Discovery of FNDR-20123, a histone deacetylase inhibitor for the treatment of Plasmodium falciparum malaria - Vijay Potluri; Radha K. Shandil; R. Gavara; Ganesh Sambasivam; Brice Campo; Sergio Wittlin; Shridhar Narayanan (Malaria Journal, 2020)
Abstract Background Emergence of anti-malarial drug resistance and perpetual increase in malaria incidence necessitates the development of novel anti-malarials. Histone deacetylases (HDAC) has been shown to be a promising target for malaria, despite this, there are no HDAC inhibitors in clinical trials for malaria treatment. This can be attributed to the poor pharmacokinetics, bioavailability and selectivity of the HDAC inhibitors. Methods A collection of HDAC inhibitors were screened for anti-malarial activity, and the best candidate was profiled in parasite-killing kinetics, growth inhibition of sensitive and multi-drug resistant (MDR) strains and against gametocytes. Absorption, distribution, metabolism and excretion pharmacokinetics (ADME-PK) parameters of FNDR-20123 were determined, and in vivo efficacy was studied in a mouse model for Plasmodium falciparum infection. Results A compound library of HDAC inhibitors (180 in number) was screened for anti-malarial activity, of which FNDR-20123 was the most potent candidate. The compound had been shown to inhibit Plasmodium HDAC with IC50 of 31 nM and human HDAC with IC50 of 3 nM. The IC50 obtained for P. falciparum in asexual blood-stage assay was 42 nM. When compared to atovaquone and pyrimethamine, the killing profiles of FNDR-20123 were better than atovaquone and comparable to pyrimethamine. The IC50 values for the growth inhibition of sensitive and MDR strains were similar, indicating that there is no cross-resistance and a low risk of resistance development. The selected compound was also active against gametocytes, indicating a potential for transmission control: IC50 values being 190 nM for male and > 5 µM for female gametocytes. FNDR-20123 is a stable candidate in human/mouse/rat liver microsomes (> 75% remaining post 2-h incubation), exhibits low plasma protein binding (57% in humans) with no human Ether-à-go–go-Related Gene (hERG) liability (> 100 µM), and does not inhibit any of the cytochrome P450 (CYP) isoforms tested (IC50 > 25 µM). It also shows negligible cytotoxicity to HepG-2 and THP-1 cell lines. The oral pharmacokinetics in rats at 100 mg/kg body weight shows good exposures (Cmax = 1.1 µM) and half-life (T1/2 = 5.5 h). Furthermore, a 14-day toxicokinetic study at 100 mg/kg daily dose did not show any abnormality in body weight or gross organ pathology. FNDR-20123 is also able to reduce parasitaemia significantly in a mouse model for P. falciparum infection when dosed orally and subcutaneously. Conclusion FNDR-20123 may be a suitable candidate for the treatment of malaria, which can be further developed.